Opponents and Identity in the Letter to the Philippians. - Nina Nikki (Novum Testamentum, Supplements, 2019)
Guided by awareness of the problematic relationship between polemical text and history, Opponents and Identity in Philippians seeks to establish a historical context for the letter to the Philippians. The study re-evaluates the relationship between Paul and the Jerusalem-based Christ-believing community from the time of the Jerusalem meeting and the Antioch incident. A more detailed analysis centers on how this relationship is reflected in Philippians. The book argues that Paul was continuously on problematic terms with the Jerusalem community, which means that they are the Jewish Christ-believing opponents referred to at several places in Philippians as well. With the help of the social identity approach (SIA), the book illustrates how Paul engages in identity formation through polemical rhetoric in his last letter.